Desenvolvimento e efeito do peso adicional no comportamento exploratório manual de lactentes pré-termo tardios - Soares, Daniele de Almeida (2011)
Background: During the first year of life, the human infant learns fundamental behaviors, such as reaching and manipulating, which will be extensively performed to explore objects. This exploration is performed by means of diversified manual actions, which may be influenced by organic immaturity, such as late prematurity, and by external perturbations, such as addition of weight load on upper limbs. Objective: This work had as general aim to verify the manual exploratory behavior in late preterm infants and full-term infants from 5 to 7 months of age, with and without additional weight load on wrists. Methods: Nine low-risk preterm infants (5 male) with minimal and maximal gestational ages of, respectively, 34 and 36 weeks and 6 days (M =35.6 ± 0.5) and mean birth weight of 2.960±0.25 kilograms, and 10 healthy fullterm infants (4 male) with minimal and maximal gestational ages of, respectively, 38 and 42 weeks (M =39.0 ± 0.73) and mean birth weight of 3.363 ± 0.14 kilograms, participated in this research. The infants were evaluated longitudinally at 5, 6 and 7 months of age (corrected to the preterm infants). The infants were placed in a baby chair reclined 50º from the horizontal and were tested in two experimental conditions: without the use of weight load (A) and with the use of weight load (B). During condition A, an attractive, silent and malleable rubber object, unfamiliar to the infants, was presented by the examiner at the infant s midline for 120 seconds. The infant could freely explore the object by up to 20 seconds or up to drop it. During condition B the same procedure conducted during condition A was carried out, however a bracelet weighting 20% of total arm mass was attached to the infant's both wrists. The evaluations were recorded by three digital cameras and analyzed frame by frame. The manual exploratory actions were coded as Fingering, Mouthing, Waving, Banging on the Object, Banging the Object, Transferring, Rotating, and Alternating. Results: The age of 7 months seemed to represent a gain in frequencies of actions Fingering, Waving, Banging-the-object and Rotating in preterm infants. They performed a lower frequency of action Mouthing compared to full-term infants at all ages (p<0.05). There were no significant differences (p>0.05) between conditions A and B in any studied variable, regardless of group or age. Conclusions: There were a decrease in the frequency of Fingering and an increase in the frequencies of Waving, Banging the Object and Rotating in both groups in the studied age. Although the preterm infants have seemed to mouth the object less than the full-term infants, in general the manual exploratory behavior was similar between the groups. Furthermore, the somatossensory and mechanical stimulus provided by the weight load was irrelevant to the frequency of performance of the exploratory actions, presenting a stabilizer effect on them in both studied groups. The late prematurity did not interfere in the infants motor responses as a function of the additional weight load at the studied age.